The Effect of Android Game-Based Learning Media on Student Learning Outcomes in Terms of Self-Directed Learning - Solihah, Mar'attus (Journal of Educational Chemistry (JEC), 2023)
The aim of this study was to investigate the effect of android-based game learning media on student learning outcome in terms of self-directed learning. This study conducted in experimental research using two-way Anova design with student learning outcome as the dependent variable. The independent variable in this study is the use of Android game-based learning media in acid and base. A total 45 students at SMA N 2 Wonosari participated in this study, consisting of 21 students in the experimental group and 24 students in control group. This sample drawn by cluster random technique. The treatment group received learning with the assist of android game-based media while the control group only used textbooks conventionally. Student learning outcomes are measured using multiple choice questions. This instrument was tested before being used to examine the validity and reliability. To test the hypothesis analisys of variance test was being carried out. Result for the main hypothesis shows that there are differences between experimental group and control group on student learning outcome. Class that used android game-based learning media gain higher cognitive learning outcome than the conventional class. There are no differences in student learning outcome at any level of student self-directed learning. Also there are no interaction between student self-directed learning and student learning outcome.